Absolute Accurate Calibration of a Robotic C-Arm System based on X-Ray Observations using a Kinematic Model - Thürauf, Sabine; Hornung, Oliver; Körner, Mario; Vogt, Florian; Nasseri, M. Ali; Knoll, Alois (ICRA 2017 Workshop C4 Surgical Robots: Compliant, Continuum, Cognitive, and Collaborative, 2017)

Accurate and Efficient Calibration of a Robotic C-Arm System Based on X-Ray Observations - Thürauf, Sabine (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

A realistic X-ray simulation for C-Arm geometry calibration - Thürauf, Sabine; Wolf, Markus; Korner, Mario; Vogt, Florian; Hornung, Oliver; Nasseri, M. Ali; Knoll, Alois (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2016)
Applications like cone beam computed tomographies (CBCTs) or 2D-3D overlays need a high geometrical accuracy of the C-Arm system. In order to achieve this, geometry calibrations are performed to increase the accuracy given by the kinematics of the system. Commonly X-ray images of a phantom with known geometry are taken for the calibration. The images, together with a 3D model of the phantom, serve as input for an optimizer, which estimates the pose of the C-Arm relative to the phantom. Afterwards, the estimates are used to increase the geometrical accuracy of the system.
Created from Fastlane, Scopus look-up

C-arm unleashed: Intuitive inter-operative positioning of C-arms using wearable gesture detection - Ouyang, Jingyu; Egle, Fabio; Igney, Claudia; Mutzke, Thomas; Dahmani, Chiheb; Castellini, Claudio; Thürauf, Sabine (BioRob 2024, 2024)

Environment effects at phantom-based X-ray pose measurements - Thürauf, Sabine; Korner, Mario; Vogt, Florian; Hornung, Oliver; Nasseri, M. Ali; Knoll, Alois (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2017)
Image-based pose measurements relative to phantoms are used for various applications. Some examples are: tracking, registration or calibration. If highly precise measurements are needed, even changes of environment factors influence the measurements.
Created from Fastlane, Scopus look-up

Evaluation of a 9D-Position Measurement Method of a C-Arm Based on X-Ray Projections - Thürauf, Sabine; Hornung, Oliver; Körner, Mario; Vogt, Florian; Nasseri, M. Ali; Knoll, Alois (MICCAI 2015 Workshop on Interventional Microscopy, 2015)
For features like X-ray CTs (computed tomography) a high absolute pose accuracy of the C-arm system is needed. Therefore, an extensive calibration has to be performed to make the C-arm system sufficiently accurate. One new approach to calibrate the system is to perform an absolute robot calibration with end effector pose measurements as input. To measure the poses, X-ray images of a calibration phantom can be used. This work determines a lower bound for an X-raybased 9D-position measurement technique for a C-arm system (including the 3D-position of the tube, the 3D-position of the detector and the 3D-orientation of the detector) using a helical calibration phantom regarding its accuracy by a simulation.<br

Experimental evaluation of the accuracy at the C-arm pose estimation with x-ray images - Thürauf, Sabine; Vogt, Florian; Hornung, Oliver; Korner, Mario; Nasseri, M. Ali; Knoll, Alois (2016)
C-arm X-ray systems need a high spatial accuracy for applications like cone beam computed tomography and 2D/3D overlay. One way to achieve the needed precision is a model-based calibration of the C-arm system. For such a calibration a kinematic and dynamic model of the system is constructed whose parameters are computed by pose measurements of the C-arm. Instead of common measurement systems used for a model-based calibration for robots like laser trackers, we use X-ray images of a calibration phantom to measure the C-arm pose. By the direct use of the imaging system, we overcome registration errors between the measurement device and the C-arm system. The C-arm pose measurement by X-ray imaging, the new measurement technique, has to be evaluated to check if the measurement accuracy is sufficient for the model-based calibration regarding the two mentioned applications. The scope of this work is a real world evaluation of the C-arm pose measurement accuracy with X-ray images of a calibration phantom using relative phantom movements and a laser tracker as ground truth.<br
Keywords: Phantoms; Measurement by laser beam; X-ray imaging; X-ray lasers; Calibration; Measurement uncertainty; Tracking

Model-Based Calibration of a Robotic C-Arm System Using X-Ray Imaging - Thürauf, Sabine; Hornung, Oliver; Körner, Mario; Vogt, Florian; Knoll, Alois; Ali Nasseri, M. (Journal of Medical Robotics Research, 2018)
In interventional radiology or surgery, C-arm systems are typical imaging modalities. Apart from 2D X-ray images, C-arm systems are able to perform 2D/3D overlays. For this application, a previously recorded 3D volume is projected on a 2D X-ray image for providing additional information to the clinician. The required accuracy for this application is 1.5mm. Such a spatial accuracy is only achievable with C-arms, if a calibration is performed. State-of-the-art approaches interpolate between values of lookup tables of a sampled Cartesian volume. However, due to the non-linear system behavior in Cartesian space, a trade-off between the calibration effort and the calibrated volume is necessary. This leads to the calibration of the most relevant subvolume and high calibration times. We discuss a new model-based calibration approach for C-arm systems which potentially leads to a smaller calibration effort and simultaneously to an increased calibrated volume. In this work, we demonstrate that it is possible to calibrate a robotic C-arm system using X-ray images and that a static model of the system is required to achieve the desired accuracy for 2D/3D overlays, if re-orientations of the system are performed.
Created from Fastlane, Scopus look-up
Keywords: C-arm system; Robot calibration; X-ray

Tuning of X-Ray Parameters for Noise Reduction of an Image-Based Focus Position Measurement of a C-Arm X-Ray System - Thürauf, Sabine; Vogt, Florian; Hornung, Oliver; Körner, Mario; Nasseri, M. Ali; Knoll, Alois (IROS 2015 Workshop on Alternative Sensing for Robot Perception: Beyond Laser and Vision., 2015)